Hyphenone A, the first 3, 3-diisoprenylated bicyclic polyprenylated acylphloroglucinols as Cav3.1 T-type calcium channel inhibitor from Hypericum henryi. Issue 45 (7th November 2019) - Jiang, Na-Na; Du, Shu-Zong; Ye, Yan-Song; Yan, Hui; Yang, Xing-Wei; Yang, Jian; Nian, Yin; Xu, Gang
Graphical abstract: Highlights: Hyphenone A (1 ), the first 3, 3-diisoprenylated PPAP was isolated from H. henryi . Compound 1 could be biosynthetically derived from an unreported precursor. It's the first report of PPAP as Cav3.1 T-type calcium channel inhibitor. Abstract: Hyphenone A (1 ), a new type of bicyclic polyprenylated acylphloroglucinols (BPAPs) featured with an unprecedented 3, 3-diisoprenylated 1, 3, 5-trione core, were characterized from the roots of Hypericum henryi together with two new congeners (hyphenones B–C, 2 –3 ) and five known biosynthetic related PPAPs. Biogenetically, 1 should be derived from a novel 3, 3, 5, 5-tetraisoprenylated MPAPs precursor. Their structures were elucidated by comprehensive spectroscopic data and X-ray diffraction. Moreover, 1 –3 were identified as the first PPAPs type Cav 3.1 T-type calcium channel (TTCC) inhibitors, with IC50 values of 7.07, 6.19, and 5.47 μ M, respectively.